Hematologic toxicity profiles and the impact of hemoglobin nadir and transfusion on oncologic outcome in definitive radiochemotherapy for cervical cancer - Meixner, Eva; Wermes, Laura; Hoeltgen, Line; Dinges, Lisa A.; Sandrini, Elisabetta; Harrabi, Semi B.; Seidensaal, Katharina; Hoegen-Saßmannshausen, Philipp; Vinsensia, Maria; König, Laila; Arians, Nathalie; Debus, Jürgen; et al. (Cancers, 2024)
Background/Objectives: Definitive radiochemotherapy with concomitant cisplatin 40 mg/m2 weekly represents the standard of care for locally advanced cervical cancer. Current studies (KEYNOTE-A18 and INTERLACE) are intensifying this regimen at the cost of increased hematologic toxicity. We aimed to evaluate influencing factors on hematotoxicity to ensure the safe application of radiochemotherapy. Methods: We retrospectively analyzed 147 patients, who received definitive radiochemotherapy between 2000 and 2019 and evaluated laboratory parameters before, after, and at each chemotherapy cycle to evaluate the occurrence, course, and profile of hematotoxicity. Further, we assessed the impact of hemoglobin levels and transfusion on oncological outcomes. Results: In a high-risk cervical cancer population with 82.3% of women with FIGO ≥ III stage, the 1-, 2-, and 5-year rates of overall survival (OS) were 89.1%, 74.7%, and 63.3%, and local control (LC) rates were 90.1%, 86.1%, and 75.0%, respectively. Grade 3 leukopenia was present in 2.1% and grade 3 anemia in 4.3%. No higher grade ≥ 4 hematotoxicity was observed. Absolute hemoglobin levels significantly reduced after the fourth cycle, with a median time from the start of therapy to hemoglobin nadir of 36 days. A lower hemoglobin nadir (<9 g/dL) was significantly associated with inferior LC. Red blood cell transfusion was applied in 44.9% of the women; the necessity of transfusion was significantly correlated to inferior OS, LC, and distant control. Conclusions: Our results suggest the need for special consideration of increased hematotoxicity and consistent implementation of anemia therapy, particularly from the fourth RT week onwards, to enable full-course definitive radiochemotherapy for locally advanced cervical cancer patients.
Gesehen am 01.05.2025